1986
DOI: 10.1366/0003702864507738
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Studies on Neutron-Irradiated Rare Earth Oxide Powers

Abstract: The effect of neutron irradiation on the photoacoustic spectra of Er2O3 and Nd2O3 in powder form has been studied. The irradiation shows a quenching effect on the photoacoustic signal which regains its intensity after a lapse of some time. It is believed that the irradiation changes the oxidation state of the rare-earth ions from M3+ to M2+. The half-life of the recovery process Er2+ to Er3+ in the case of irradiated Er2O3 is found to be 46 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…Zang et al [29] reported that Yb 3+ changes to Yb 2+ after γ irradiation in YAG crystal, which recovers after annealing. Similar changes in valency of Nd 3+ to Nd 2+ have been reported by Rai et al [16,24] in neutron irradiated Nd 2 O 3 powder and gamma irradiated Nd doped phosphate glasses. Most of the above reports are made on the basis of UV and visible spectroscopy.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Zang et al [29] reported that Yb 3+ changes to Yb 2+ after γ irradiation in YAG crystal, which recovers after annealing. Similar changes in valency of Nd 3+ to Nd 2+ have been reported by Rai et al [16,24] in neutron irradiated Nd 2 O 3 powder and gamma irradiated Nd doped phosphate glasses. Most of the above reports are made on the basis of UV and visible spectroscopy.…”
Section: Introductionsupporting
confidence: 86%
“…It has been established that most of the glasses produce various interesting changes in their properties, when irradiated by high energy particles or radiation such as UV, γ rays and neutrons [15][16][17][18][19][20][21][22][23][24]. The irradiation effect produces changes in the optical properties of glasses in the form of generation of some new absorption bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zang et al [41] reported that Yb 3+ changes to Yb 2+ after  irradiation in YAG crystal, which recovers after annealing. Similar changes in valence state of Nd 3+ to Nd 2+ have been reported by Rai et al [28,36,42] in neutron irradiated Nd 2 O 3 powder and gamma irradiated Nd doped phosphate glasses. Generation of other types of defects such as oxygen vacancies and color centers have also been reported earlier [37][38][39].…”
Section: Introductionsupporting
confidence: 85%
“…high-energy radiation (X-rays, ')'-rays, ultraviolet light and neutrons) on materials generally produce various interesting changes in their properties, which include physical, chemical, electrical, magnetic, mechanical as well as optical properties[5]-[14]. These radiations mainly produce ionization and displacement in the constituent elements of the samples.Ionization effects disappear fast in the case of good conductors and produce heating in the materials, whereas in insulators, electrons produced by ionization get trapped in the lattice imperfections producing permanent changes in the material.…”
mentioning
confidence: 99%